External Inflammatory Root Resorption in Traumatized Immature Incisors: MTA Plug or Revitalization? A Case Series - Boukpessi, Tchilalo; Cottreel, Leslie; Galler, Kerstin Martina (Children, 2023)
Introduction: External inflammatory root resorption (EIRR) in immature permanent teeth is a common complication after severe dental trauma. The management of this condition requires thorough disinfection of the root canal in order to arrest the resorptive process. However, current guidelines regarding the recommended treatment of EIRR following traumatic dental injuries vary, mainly in regard to the type of intracanal medication and its retention time in the root canal system. The objective of this case series was to present both the apical barrier technique (MTA plug) and revitalization procedures as valid treatment options in immature teeth with EIRR. Methods: Four cases of post-traumatic immature teeth diagnosed with pulp necrosis and EIRR, with or without apical periodontitis, were treated either by an MTA plug (two teeth) or revitalization (two teeth). Cases were followed between 12 and 24 months. Results: Both treatment methods were efficient in arresting EIRR and enabled bone healing. After revitalization, partial root maturation was observed. Conclusion: Whereas the key to achieve periodontal healing in cases of EIRR is thorough disinfection of the root canal, both a subsequent MTA plug as well as revitalization may represent adequate treatment methods. An additional benefit lies in the potential of revitalization to promote further root maturation through hard tissue apposition.
CRIS-Team Scopus Importer:2023-09-15
Keywords: case series; dental trauma; immature teeth; MTA plug; pulp necrosis; revitalization